2003
DOI: 10.1007/s00709-002-0045-4
|View full text |Cite
|
Sign up to set email alerts
|

Development of Cuscuta species on a partially incompatible host: induction of xylem transfer cells

Abstract: The growth of dodders, Cuscuta reflexa and Cuscuta japonica, on the partially incompatible host poinsettia ( Euphorbia pulcherrima) is studied. Poinsettia responds by bark growths to the formation of the dodder haustoria and prevents dodder from obtaining normal growth. The growth instead becomes extremely branched, coral-like, and dodder lacks the ability to form haustoria. After a period of coral-like growth, long shoots sprout, resembling the normal growth. These long shoots mark an ending phase for dodder,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
21
0

Year Published

2004
2004
2023
2023

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(23 citation statements)
references
References 22 publications
2
21
0
Order By: Relevance
“…Hypertrophy and increase in the number of vascular bundles in Momordica stems was clearly induced by Cuscuta hypae. No previous reports of vascular tissue differentiation caused by plantÁ plant interactions (especially induced by Cuscuta hypae) are available, although vascular tissue development of Cuscuta itself has been studied (Christensen et al 2003). Interestingly, we observed similar hypertrophy in interactions between Cuscuta and other members of the Cucurbitaceae family (e.g.…”
Section: Morphological Change and Vascular Bundle Differentiation Insupporting
confidence: 64%
“…Hypertrophy and increase in the number of vascular bundles in Momordica stems was clearly induced by Cuscuta hypae. No previous reports of vascular tissue differentiation caused by plantÁ plant interactions (especially induced by Cuscuta hypae) are available, although vascular tissue development of Cuscuta itself has been studied (Christensen et al 2003). Interestingly, we observed similar hypertrophy in interactions between Cuscuta and other members of the Cucurbitaceae family (e.g.…”
Section: Morphological Change and Vascular Bundle Differentiation Insupporting
confidence: 64%
“…Ultrastructural studies have indicated that dodder-searching hyphae contacting host sieve elements differentiate into transfer cells, but do not make open connections to the host phloem (Dö rr, 1990). Thus, it has been proposed that content of the host phloem must cross host and parasite membranes in an apoplastic transfer process (Christensen et al, 2003). However, Birschwilks et al (2006) argue that their observed rates of radiolabeled metabolite, dye, and virus translocation from host to dodder can only be explained by symplastic transport.…”
Section: Discussionmentioning
confidence: 99%
“…More recently, such radiotracers have been replaced by xylem-and phloemspecific fluorescence reagents (e.g. Texas red and Carboxyfluorescein) (Haupt et al 2001;Christensen et al 2003;Birschwilks et al 2007).…”
Section: Introductionmentioning
confidence: 99%